Impacts of irrigation with sugar mills’ wastewater and fertilizer on soil chemical and solute-transport properties (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Impact assessment of wastewater on soil is important to diagnose the potential of wastewater irrigation. By taking this idea into consideration, an experiment was conducted to investigate the chemical and solute-transport properties of soils collected from wheat fields irrigated with sugar mills’ wastewater at North Bengal Sugar Mill (NBSM) and Faridpur Sugar Mill (FSM) of Bangladesh. Soil samples were collected from experimental sites where wheat was grown under both irrigation and fertilizer treatments. The split-plot design with three replications of irrigation (main plot) and fertilizer (sub-plot) were used. Irrigation and fertilizer treatments were defined as I1 = irrigation with fresh water, I2 = irrigation with mixed water (fresh water: wastewater = 1:1) and I2 = irrigation with wastewater; F1 = Full dose fertilizer, F2 = Half dose fertilizer and F3 = No application of fertilizer. Soil samples were chemically analyzed to find their chemical properties and a breakthrough experiment was done to find the solute transport properties. Significant effects were observed for soil chemical properties at both NBSM and FSM sites. At NBSM site, organic-C and S contents of soil increased under I3 treatment, where as total-N, P, K and Mg contents increased under I2 treatment. Similarly, Na and Ca contents at FSM site slightly went downunder I3 treatment. Application of fertilizer also significantly affected soil properties at both sites. Under full dose fertilizer application (F1) EC, P, K, S, Ca and Mg contents of the soil increased, however, Na content decreased at both sites. Interaction of irrigation and fertilizer treatments also had significant effects on all the soil chemical parameters except organic-C and total-N content of the soils at both sites. Among solute transport properties pore-water velocity, dispersion coefficient and mean solute travel time increased in I3 compared to I1 at NBSM site, but the reverse was observed at FSM site.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 521-532